Association between Sarcopenia and Insulin-Like Growth Factor-1, Myostatin, and Insulin Resistance in Elderly Patients Undergoing Hemodialysis - Novira Widajanti; SoebagijoAdi Soelistijo; Usman Hadi; Mochammad Thaha; null Aditiawardana; null Widodo; Hadiq Firdausi; YafanitaIzzati Nurina; MiraDelima Asikin; Hersih Srinowati; NoerHalimatus Syakdiyah (Journal of Aging Research)
Sarcopenia is common in hemodialysis patients, especially in the elderly patients undergoing hemodialysis. Various factors may contribute to the occurrence of sarcopenia, such as anabolic and catabolic imbalance. This study aims to investigate the correlation of insulin-like growth factor-1 (IGF-1) levels as an anabolic factor, myostatin levels, and insulin resistance as catabolic factors with sarcopenia in the pathogenesis of sarcopenia in elderly patients undergoing hemodialysis. A total of 40 subjects aged 60 years or more who undergoing hemodialysis in Dr. Soetomo Hospital Surabaya were included in this cross-sectional study. Sarcopenia was diagnosed according to Asian Working Group Sarcopenia 2019 criteria. IGF-1, myostatin, and insulin resistance levels were measured once before hemodialysis. Subjects with sarcopenia diagnosis were 33 (82.5%), that is, 19 (47.5%) men and 14 (35%) women. There were 28 (70%) of the subjects diagnosed with severe sarcopenia. Furthermore, there were significant differences in the characteristics and geriatric parameters between the sarcopenia and nonsarcopenia groups. There were differences between the two groups in hemoglobin levels, IGF-1 levels, myostatin levels, homeostasis model assessment-insulin resistance (HOMA-IR) levels, muscle mass, handgrip strength, body mass index status, mini nutritional assessment status, and physical activity scale for elderly status (all p < 0.05). Correlation analyses showed that IGF-1 levels negatively correlated with sarcopenia status in elderly patients undergoing hemodialysis (p < 0.05). On the contrary, myostatin and HOMA-IR levels were positively correlated with sarcopenia status in elderly patients undergoing hemodialysis (all p < 0.05). Based on this recent study, IGF-1, myostatin, and insulin resistance were significantly correlated with sarcopenia in elderly patients undergoing hemodialysis.